Mechanism of interface morphology of YSZ thermal barrier coating on growth behavior of TGO layer - TANG Jianjiang; YU Fangli; ZHANG Haihong; BAI Yu; WANG Junwen; LIU Yanling (Journal of Aeronautical Materials, 2019)
The mechanism of coating interface bulge on the TGO growth behavior was studied by analyzing the rule of TGO growth and the interface stress at the top coat/bond coat interface. The results show that the growth rate of TGO in the convex region of the top coat/bond coat interface is higher than that in the other regions. According to the stress analysis of ANSYS, the interface stress increases (from 185 MPa to 406 MPa) with the increase of roughness (from 10 μm to 20 μm). Additionally, the interfacial stress also increases (from 142 MPa to 574 MPa) with the thickness of TGO layer increasing (from 1.6 μm to 9.3 μm). What’s more, during high temperature oxidation, the convex region of the top coat/bond coat interface is mainly characterized by tensile stress and the depressed region is compressive stress.The tensile stress can promote the rapid growth of TGO layer, while the compressive stress exhibits the inhibition on the growth rate of TGO. In summary, reducing the roughness of bond coat can reduce the interface stress and slow the growth rate of TGO, which ensures the effective bonding strength of the coating. Thus, the stability of the TBCs at high temperature can be improved.